Effect of Smartphone-Assisted Jigsaw Cooperative Learning on Students’ Mathematics Self-Efficacy - Johnson, Felicia Omotola; Lawal, Ruth Folake; Dada, Favour Hapuruchi (S&Co Publishing, 2023)
Smartphones have become handy tools in the hands of 21st-century teenagers owing to their necessity for communication and socialization. These devices could therefore possess underlying benefits for mathematics education. This quasi-experimental study probed the consequence of smartphone-assisted Jigsaw cooperative learning on senior secondary school students’ mathematics self-efficacy with recourse to how gender and smartphone efficacy could moderate this effect. The study involved five research questions and hypotheses. Two schools from the Educational District IV, Lagos State were selected by purposive sampling technique from which five hundred and thirty four (534) students drawn from intact classes were assigned into experimental and control groups. Smartphone Assisted Learning Package (SALP) served as the intervention while a valid and reliable Mathematics Self-Efficacy Questionnaire (r=0.90) was employed for data collection. Statistical tools deployed for descriptive and inferential analysis include mean, standard deviation and Analysis of covariance (ANCOVA). Outcome of data analysis portrayed a momentous effect of treatment on students’ mathematics self-efficacy. Smartphone efficacy and gender were found to possess substantial influence on participants’ mathematics self-efficacy. These findings led to the recommendation that teachers should expose mathematics students to smartphone-assisted Jigsaw cooperative learning strategy to promote active learning and improve students’ mathematics self-efficacy.